Experiments with the Concept of Authenticity in Studio Pedagogy: Designing with Precedents - Sevgi Türkkan; Arzu Erdem (Megaron, 2016)
Architectural education, like architectural culture, is charged with responsibility for traditions, rituals, pedagogical models, and norms that place great importance on authenticity. Authenticity, meaning originality or genuineness as well as referring to an individual's creative faculties, is a fundamental concept that distinguishes the designer's capabilities in a creative process. Situated at the core of architectural education, the design studio has long been serving as an environment for the semi-god creator to invent his 'authentic' designs ex-nihilo. The prevalent conception of authenticity is a romanticized one, where unique forms are a means of personal expression and exterior influences are intruders into one's true creativity. Although 'authenticity' was subjected to heavy criticism during the 20th century in various fields, it continues to shape pedagogical tendencies in architectural education today. Taboos on formal similarity, repetition, and ordinariness continue to pressure studio culture. One of the pedagogical implications of this obsession with 'authenticity' is to restrict interaction with precedents in design education. It is worth asking if subverting these taboos on authenticity enhances design studio learning. Is it possible to re-approach precedents as found objects, and manipulation as a tool for alternative modes of creativity and learning in the studio environment? Two design experiments have been devised to rethink authenticity and creation in studio pedagogy, and to experiment with manipulation of precedents as a potential learning and designing resource. It is not intended to neglect or overthrow the concept of 'authenticity' in the design studio, but to reassess it with a critical pedagogical approach that acknowledges architectural qualities other than the purely formal.